Interaction between the society around forest area with the use of biodiversity in the natural forest ecosystem of Bedugul-Pancasari, Bali - BRAMANTYO TRI ADI NUGROHO; NI KADEK EROSI UNDAHARTA; MUSTAID SIREGAR (Society for Indonesian Biodiversity, 2008)
Natural ecosystem forest of Bedugul-Pancasari represents an area which located in Tabanan regency, Bali province. This ecosystem area consist of eight laid orchard at strategic area so that do not deny by many society forest exploit variety involve residing in the area. This research aimed to get the information about variance factors that influence the extraction of nature resources by the village and also to know the respondent characteristic. The result from frequency distribution table showed the age of respondent 20-35 (45%) was the biggest group which taken the forest biodiversities around Bedugul-Pancasari forest. The respondent who taken the biggest forestbiodiversity has income from 50,000-185,000 rupiahs (42%) and 82% as a farmer. The age, the distance between house and forest, and the number of family member variables influenced the respondents to take the forest biodiversities. The Cramerâ€™s V value for each variable is 0.592, 0.691 and 0.723 that indicated there was correlation.Â© 2008 Jurusan Biologi FMIPA UNS Surakarta.Key words: society interaction, Bedugul-Pancasari, forest.